2020
DOI: 10.3892/etm.2020.8604
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA GACAT3 promotes liver cancer progression by regulating the proliferation, apoptosis and migration of tumor cells

Abstract: Long non-coding RNA gastric cancer associated transcript 3 (GACAT3), is a newly identified non-coding RNA, which has been found to be involved in the tumorigenesis of gastric cancer. However, the biological function of GACAT3 in liver cancer remains unclear. The present study aimed to determine the expression level and function of GACAT3 in liver cancer. The authors cultured liver cancer cells in vitro and GACAT3 was silenced in the cells. Cell proliferation, apoptosis and migration were determined by MTT assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The effects were also supported by the results of western blot analysis, in which GACAT3 suppressed the expression of PCNA while enhanced the cleaved caspase 3 and cleaved PAPR. These results were consistent with that from studies on tumours [32,27]. Thus, we speculated that GACAT3 was involved in the OA pathology, and meanwhile its upregulation in chondrocytes may promote OA progression.…”
Section: Discussionsupporting
confidence: 92%
“…The effects were also supported by the results of western blot analysis, in which GACAT3 suppressed the expression of PCNA while enhanced the cleaved caspase 3 and cleaved PAPR. These results were consistent with that from studies on tumours [32,27]. Thus, we speculated that GACAT3 was involved in the OA pathology, and meanwhile its upregulation in chondrocytes may promote OA progression.…”
Section: Discussionsupporting
confidence: 92%
“…Hepatocellular carcinoma (HCC) is the most common type of liver cancer ( Anwanwan et al, 2020 ), and overexpression of many lncRNAs in hepatocytes contributes to carcinogenesis in HCC ( Wang et al, 2017 ; Feng et al, 2019 ; Zhang et al, 2019 ; Zhang et al, 2020b ). GACAT3 is aberrantly overexpressed in HCC tissues and liver cancer cell lines, including HepG2, HCCLM3, SK-Hep-1, SMMC-7721, and Huh7 ( Dong et al, 2020 ; Li et al, 2020 ). Importantly, GACAT3 is associated with lower OS and disease-free survival in HCC patients ( Dong et al, 2020 ).…”
Section: Expression Of Gacat3 In Cancermentioning
confidence: 99%
“…Tumor xenograft experiment. HCT116 cells (2x10 6 ) stably transfected with sh-LINC01535 or sh-NC were subcutaneously injected subcutaneously into the left flank of 6-week-old female nude mice (n=5 mice per group; weight, ~20 g). For the animal study, humane endpoints were utilized to prevent unnecessary animal suffering according to the Guide for the Care and Use of laboratory Animals from the National Institutes of Health.…”
Section: Rna-binding Protein Immunoprecipitation (Rip) Assay Thementioning
confidence: 99%
“…Long noncoding RNA (lncRNA) is a class of transcripts with >200 nucleotides in length (4,5). Accumulating evidence has indicated that lncRNAs have crucial roles in various biological processes (6)(7)(8). Furthermore, emerging studies have suggested that lncRNAs have important roles in the initiation and progression of human cancers (9,10).…”
Section: Introductionmentioning
confidence: 99%